Synthesis of copper nanowires via a liquid phase reduction process. Issue 183 (2nd September 2017) - Guangming, Wu; Dan, Li; Jianxiang, Yu; Dongdong, Feng
ABSTRACT: Copper nanowires (Cu NWs) were successfully synthesized via a method of liquid phase reduction by using hydrazine hydrate as reducing agent, ethylenediamine (EDA) as structure-directing agent. The impact of various factors on Cu NWs was analyzed by orthogonal experiment. Cu NWs were characterized by SEM, XRD, and TEM techniques. The results show that: the Cu NWs were free of oxidation, and were highly oriented along the (111) direction. The sequence of factors which impact the length and diameter of Cu NWs is: hydrazine hydrate - NaOH - EDA - reaction temperature. Considering all the factors, to synthesize Cu NWs, the optimal conditions are as follows: 4mL EDA, 50mL NaOH, 10 mL1% hydrazine hydrate, 10 mL 10% hydrazine hydrate, 80°C.